Origin of discordant U Pb dates in non-metamict zircons in intrusives deformed at granulite facies: Grain scale processes, and relevance to Cambrian orogeny, Eastern Ghats Belt, India - Banerjee, Anwesa; Piazolo, Sandra; Cogne, Nathan; Bhattacharya, Abhijit; Prabhakar, N. (Chemical Geology, 2024)
International audience